Bacillus cereus group: genetic aspects related to food safety and dairy processing - Rossi, Gabriel Augusto Marques [UNESP]; Aguilar, Carlos Eduardo Gamero [UNESP]; Silva, Higor Oliveira [UNESP]; Vidal, Ana Maria Centola (Instituto Biológico, 2018)
Bacillus cereus group includes not pathogenic and high pathogenic species. They are considered as a risk to public health due to foodborne diseases and as an important cause of economic losses to industries due to production of spoilage enzymes. Some researches have been performed in order to assess the possible factors that contribute to put public health into risk because of consumption of food contaminated with viable cells or toxins which have complex mechanisms of production. The control of these bacteria in food is difficult because they are resistant to several processes used in industries. Thus, in this way, this review focused on highlighting the risk due to toxins production by bacteria from B. cereus group in food and the consequences for food safety and dairy industries.

Diversas espécies fazem parte do grupo de Bacillus cereus, desde algumas apatogênicas até outras com alta patogenicidade. Consistem em risco à saúde pública decorrentes de toxinfecções alimentares, além de causarem importantes perdas econômicas para as indústrias em virtude da produção de enzimas deteriorantes. O controle da contaminação em alimentos por esses micro-organismos é difícil, visto que são resistentes a vários tratamentos utilizados pelas indústrias. Assim, diante do exposto, esta revisão objetivou fornecer informações em relação aos aspectos genéticos desse grupo de bactérias e seus mecanismos de produção de toxinas, além de ressaltar a importância e as novas estratégias de controle para as companhias alimentícias e de laticínios.
Grupo do Bacillus cereus: aspectos genéticos relacionados à segurança alimentar e ao processamento de derivados lácteos
Keywords: biofilm; genome; milk; microbiology; toxins; biofilmes; genoma; leite; microbiologia; toxinas